Effect of Potassium Sorbate on Some Microbiological Properties of Cokelek Stored at Different Temperatures - Öksüztepe, Gülsüm; İlhak, O. İrfan; Dikici, Abdullah; Çalıcıoğlu, Mehmet; Patır, Bahri (My University, 2010)
In this study, the effect of potassium sorbate at 0.01%, 0.05% and 0.1% on the some microbiological (total aerobic mesophilic bacteria-TAMB, coliform bacteria, Lactobacillus-Leuconostoc-Pediococcus, Stapylococcus-Micrococcus, enterococcus and yeast-mold) and chemical (pH, acidity) properties of cokelek stored at 4±1°C or 22±1°C was investigated. It was seen that adding potassium sorbate at 0.01%, 0.05% and 0.1% to cokelek did not have an effect on numbers of TAMB, coliform bacteria, lactobacillus- leuconostoc- pediococcus, staphylococcus-micrococcus in cokelek stored at both 4±1°C and 22±1°C (P>0.05). However, adding potassium sorbate at 0.05% and 0.1% to cokelek had an effect on numbers of enterococci and yeast-mold in cokelek stored at 4±1°C (P<0.05). It was also not observed significant difference in pH and acidity levels between control group and treatment groups containing potassium sorbate during storage period (P>0.05).
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cokelek; Microbiological quality; Potassium sorbate